Palladium-Catalyzed Carbonylative Synthesis of Benzogerminones - Chen, Bo; Wu, Xiao-Feng (Synlett, 2019)
A novel and practical procedure for the synthesis of benzogerminones by carbonylative cyclization has been developed. With Pd(PPh3)4 as the catalyst and DABCO as the base, the desired benzogerminones were isolated in moderate to good yields with good functional group tolerance. To the best of our knowledge, this is the first procedure for benzogerminones synthesis.
Keywords: palladium catalyst; carbonylation; cyclization; benzogerminone; heterocycle synthesis